COMPARATIVE STUDY BETWEEN HEARTTYPE FATTY ACID-BINDING PROTEIN AND ASYMMETRIC DIMETHYLARGININE AS A RISK MARKER OF CARDIOVASCULAR DISEASES IN RATS - Marwan A. Ibrahim (European Scientific Journal, ESJ, 2014)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide. A number of comorbidities are associated with CVDs and prognosis is poor, with many patients experiencing disease progression. Recognizing the factors associated with CVDs progression enables high risk patients to be identified and given more intensive treatment if necessary. The identification of new predictive markers might improve the understanding of the pathogenesis and progression of CVDs. This study discusses a comparison between heart-type fatty acid-binding protein (H-FABP) and asymmetric dimethylarginine (ADMA) as a risk marker by induction cardiovascular problems in male adult albino rats by exposing to acute Carbon monoxide (CO) poisoning. CO intoxication causes cardiovascular problems as a result of diffuse tissue hypoxia. The rats were exposed to a mixture of either 3000 (group A) or 5000 (group B) parts per million (ppm) CO in air, or to ambient air (group C, control group). Blood samples were taken just before, immediately after and 6 hours after the exposure, and serum H-FABP and ADMA levels were measured. Serum H-FABP levels increased just after the CO exposure in both groups A and B. Additionally, H-FABP level was higher in group B than in group A, immediately after the exposure. However, plasma ADMA levels only increased at 6 hours after the CO exposure in groups A and B. The study results suggest that H-FABP might have potential to be an early and quantitative parameter of clinical severity and prognosis in CVDs.